Palladium-catalyzed cross-coupling of unactivated alkenes with Acrylates: application to the synthesis of the C13-C21 fragment of Palmerolide A - Wen, Zhen-Kang (2013)
Diene to meet: A palladium-catalyzed cross-coupling reaction between alkyl-substituted olefins and acrylates gives the corresponding butadienes in moderate yield and stereoselectivity. This atom-economical reaction, which forms Cmath image–Cmath image bonds, tolerates a wide range of allylic and homoallylic alcohols, and acrylates (see scheme; TIPS =triisopropylsilyl). The methodology was applied to the synthesis of the C13–C21 fragment of palmerolide A.